Padrões de projeto no desenvolvimento de sistemas de processamento de imagens - Welfer, Daniel (2005)
This dissertation presents software components for processing and analysis of digital images and a system capable to control them in an organized way. The Components must be functional, context-free, readable and maintainable. So far, achieving these basic requirements is a need in the software development process. Software components are designed to be reusable in a variety of different environments. The architecture of programming language used, in the case Java, allows programs to be assembled from software building blocks. In that way the designer can incorporate easily these components into an application, needing just to know your entrance and exit interface. However, to find the right abstractions to build extensible and reusable software is not an easy task. Even experienced object-oriented designers often need to review a design several times before getting to one appropriate solution. Therefore, the idea of design patterns has gained ground quickly since it provides a solution to a certain design problem. These patterns specify a way to build, structure, and manipulate software entities in a reasonably fashion, aiming mainly, to management your complexity in the domain of digital imaging processing to assure your quality. In this paper were built components for image segmentation based on convolution filters, for improvement of the quality of the image through the process of automatic equalization, for image storage in graphic files of different formats, in the creation of a component to visualize the histogram, in the visualization of the image in the screen through graphic interface, in the conversion of the colored images for grayscale formats and in the thresholding process.